2018
DOI: 10.1021/acs.bioconjchem.8b00554
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond Unpredictability: The Importance of Reproducibility in Understanding the Protein Corona of Nanoparticles

Abstract: While it is well established that the surface of a nanoparticle plays a pivotal role for the protein corona, the vast number of proteins present in biological media render general conclusions about affinities between nanoparticle surfaces and proteins nontrivial. Recently published articles increasingly reveal differences between systems and an ever increasing number of influencing factors for the protein corona. In contrast, the present study posits that the reported differences may, at least in part, be due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Thus, the size factor appears to be less determinant for protein corona composition than previously reported [24,36]. Recently, the importance of an ever-increasing number of determinant factors for the protein corona has been questioned [76]. It appeared that even very important factors such as surface chemical groups may not be as determinant as what one could assume.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the size factor appears to be less determinant for protein corona composition than previously reported [24,36]. Recently, the importance of an ever-increasing number of determinant factors for the protein corona has been questioned [76]. It appeared that even very important factors such as surface chemical groups may not be as determinant as what one could assume.…”
Section: Discussionmentioning
confidence: 84%
“…REPES analysis of the PMPC-PVBTMA system shows the growth of~200 nm aggregates over 1 to 10 h. This slight stability issue may be mitigated by increasing the degree of polymerization of PMPC, as the total length of the zwitterionic corona in micelles were previously shown to affect nanoparticle stabilization and delivery efficacy [33]. Nevertheless, because protein adsorption onto nanoparticle carriers in biological settings is a known design consideration for micelle assemblies [65,66], the prepared PCMs and zPCM show good overall resistance to destabilization by serum.…”
Section: Pcms and Zpcms In Biologically Relevant Conditionsmentioning
confidence: 99%
“…Other proteins form a dynamic layer based on the Vroman effect – high‐abundance, low‐affinity proteins are dynamically replaced by lower‐abundance higher‐affinity proteins overtime during the nano‐bio interaction [46] . Conformational changes of the adsorbed protein can result from surface curvature, topography and surface energy/hydrophobicity [47] . It has also been shown that PC composition varies depending on the environment [42,43] .…”
Section: Interaction Between Polysaccharide‐based Nanoparticles and Tmentioning
confidence: 99%
“…[46] Conformational changes of the adsorbed protein can result from surface curvature, topography and surface energy/hydrophobicity. [47] It has also been shown that PC composition varies depending on the environment. [42,43] New studies on carbohydrate nanopolymers are beginning to routinely involve PC analysis using gel electrophoresis or mass spectrometry (MS) analysis.…”
Section: Interaction Between Polysaccharide-based Nanoparticles and Tmentioning
confidence: 99%